Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s00125-004-1582-5
|View full text |Cite
|
Sign up to set email alerts
|

High-dose thiamine therapy counters dyslipidaemia in streptozotocin-induced diabetic rats

Abstract: Aims/hypothesis. Cardiovascular disease in diabetes is linked to increased risk of atherosclerosis, increased levels of triglyceride-rich lipoproteins and enhanced hepatic lipogenesis. The hepatic hexosamine pathway has been implicated in signalling for de novo lipogenesis by the liver. In this study, we assessed if decrease of flux through the hexosamine pathway induced by high-dose thiamine therapy counters diabetic dyslipidaemia. Methods. The model of diabetes used was the streptozotocin-induced diabetic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 44 publications
3
79
1
1
Order By: Relevance
“…Increased AGE and MetSO residue content of peptides in portal venous plasma was found in previous studies [30], consistent with absorption of glycated and oxidised peptides from digested food. The four-to 27-fold increase in urinary excretion of pentosidine, CML and MG-H1 free adducts in diabetic rats without similar proportional increase in food consumption found herein, however, suggests the contribution of AGEs in food to AGEs exposure is low in the diabetic state [9]. The link of urinary excretion of protein glycation, oxidation and nitration free adducts to flux of endogenous adduct formation is compromised where there is metabolism and repair of the free adducts.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Increased AGE and MetSO residue content of peptides in portal venous plasma was found in previous studies [30], consistent with absorption of glycated and oxidised peptides from digested food. The four-to 27-fold increase in urinary excretion of pentosidine, CML and MG-H1 free adducts in diabetic rats without similar proportional increase in food consumption found herein, however, suggests the contribution of AGEs in food to AGEs exposure is low in the diabetic state [9]. The link of urinary excretion of protein glycation, oxidation and nitration free adducts to flux of endogenous adduct formation is compromised where there is metabolism and repair of the free adducts.…”
Section: Discussionsupporting
confidence: 52%
“…Benfotiamine uses the reduced folate carrier-1 (RFC-1) and phosphatase activity for thiamine delivery [2]. Decreased production of RFC-1 in diabetes and loading of tissues with TMP by benfotiamine approaching levels that inhibit thiamine pyrophosphokinase may impair thiamine delivery by benfotiamine in diabetes [9,33]. Unexpectedly, benfotiamine therapy increased concentrations of plasma glycation and oxidation free adducts in diabetic rats, relating to decreased clearance and increased tubular re-uptake of AGE and MetSO free adducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been repeatedly demonstrated that thiamine and its analogue benfotiamine have the potential to correct most of the known metabolic abnormalities induced by high glucose in isolated cells [7][8][9] and to prevent microangiopathy in animals with experimental diabetes [10][11][12]. Besides, initial evidence shows a potential role for this vitamin also in the prevention of nephropathy in diabetic subjects [13].…”
Section: Introductionmentioning
confidence: 99%
“…The application of benfotiamine and the resulting activation of the enzyme transketolase in the diabetic, hyperglycemic system can also produce beneficial effects on general nerve health. Benfotiamine has been shown in many preclinical [21,[31][32][33][34][35][36][37][38][39][40][41][42][43] as well as clinical studies [44][45][46][47][48][49][50][51][52][53][54][55][56][57] to prevent the formation of AGEs [21,53] and eventually with continued treatment to reverse the symptoms associated with the neuropathy [46,47,52,57]. By increasing intracellular levels of thiamine, benfotiamine indirectly induces enzymatic and biochemical pathways [58][59][60] through elevated concentrations of thiamine diphosphate resulting in a reduced level of damaging glucose-derived chemical protein species [21,22,32,[37][38][39][60][61]…”
Section: Introductionmentioning
confidence: 99%